The impact of hiring costs for skilled workers on apprenticeship training : a comparative study - Aepli, Manuel [Verfasser]; Mühlemann, Samuel [Verfasser]; Pfeifer, Harald [Verfasser]; Schweri, Jürg [Verfasser]; Wenzelmann, Felix [Verfasser]; Wolter, Stefan C. [Verfasser] (My University, 2024)
„This study analyzes the relationship between firms’ costs of hiring skilled workers and their provision of internal apprenticeship training. Our empirical analysis draws on four waves of firm surveys conducted in Germany and Switzerland that include detailed information on firms’ hiring costs for skilled workers and training practices. Using an indicator of labor market tightness as an instrumental variable, we identify a substantial hiring cost elasticity of apprenticeship contracts of 1.4 for Swiss firms. Although we also find a positive and increasing cost elasticity for German firms over time, its magnitude is considerably smaller. Our results are consistent with the perspective that longer-term post-training benefits are more significant in a country with frictions in the labor market and contribute to a better understanding of firms’ training behavior.“ (authors‘ abstract; BIBB-Doku)
Keywords: S 5.3 Personalentwicklung; S 4 Kosten & Finanzierung; S 3.2 Unternehmen und Behörden; 370; 330; Berufsausbildung; Stellenbesetzung; Fachkräfte; Kosten; Betriebsbefragung; Schweiz; Bundesrepublik Deutschland